Strategy for the prediction, control and optimizing of the functional properties of food proteins; using statistical and chemometric tools - Barberis, Sonia Esther; Sturniolo, Héctor Luis; Folguera, Laura; Magallanes, Jorge (Elsevier, 2018)
Fil: Barberis, Sonia Esther. Universidad Nacional de San Luis. Facultad de Química, Bioquímica y Farmacia. Departamento de Farmacia. Laboratorio de Bromatología; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - San Luis. Instituto de Física Aplicada "Dr. Jorge Andrés Zgrablich". Universidad Nacional de San Luis. Facultad de Ciencias Físico Matemáticas y Naturales. Instituto de Física Aplicada "Dr. Jorge Andrés Zgrablich"; Argentina